1961
DOI: 10.1111/j.1365-246x.1961.tb02967.x
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of the Japanese Islands as inferred from Rock Magnetism

Abstract: Summary Results are presented of the directions of magnetization for twentyeight sets of rocks collected from different parts of Japan. The directions for rocks of Pre‐Tertiary age from south‐west Japan differ systematically from those from north‐east Japan. It is suggested that the difference is due to the deformation of the Japanese Islands in the late Mesozoic or early Tertiary. Because of the deformation, it is not possible to infer the accurate position of the geomagnetic dipole with respect to Japan for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

1971
1971
1999
1999

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…Clockwise deflected paleomagnetic directions in Late Cretaceous to Paleogene rocks of southwest Japan (SW Japan) were first reported by Kawai et al [1961]. Later paleomagnetic studies established that SW Japan experienced clockwise rotation in Miocene times [e.g., Otofuji, 1996 …”
Section: Introductionmentioning
confidence: 99%
“…Clockwise deflected paleomagnetic directions in Late Cretaceous to Paleogene rocks of southwest Japan (SW Japan) were first reported by Kawai et al [1961]. Later paleomagnetic studies established that SW Japan experienced clockwise rotation in Miocene times [e.g., Otofuji, 1996 …”
Section: Introductionmentioning
confidence: 99%
“…The past paleomagnetic studies done before 1970's have already revealed that remanent magnetization of the Cretaceous and Paleogene rocks in Southwest Japan shows significant declination shift relative to those in Northeast Japan (KAWAI et al, 1961;1971), and to those in the Korean Peninsula (YASKAWA, 1975). The pioneer workers suggested that the declination shift was caused by a clockwise rotation of Southwest Japan.…”
Section: Introductionmentioning
confidence: 99%
“…From the analysis of the paleomagnetic data in Japan, KAWAI et al (1961KAWAI et al ( , 1969KAWAI et al ( , 1971 concluded that the northeastern and southwestern parts of Honshu island rotated counterclockwisely and clockwisely, respectively, around a hinge in the central part of Honshu island at some time between Cretaceous and Upper Tertiary. This concept was further elaborated by additional paleomagnetic and age data from both the southwestern MATSUDA, 1983, 1984) and northeastern Japan (OTOFUJI et al, 1985;TOSHA, 1984).…”
Section: Introductionmentioning
confidence: 99%